TINGKAT PENGETAHUAN BANTUAN HIDUP DASAR (BHD) MAHASISWA KESEHATAN INSTITUT KESEHATAN DAN TEKNOLOGI AL INSYIRAH - Tengku Isni Yuli Lestari Putri; Rahmaniza Rahmaniza; Fatma Nadia (Jurnal Ilmu Kebidanan, 2023)
Emergency events outside the hospital can lead to a worsening of the victim's condition, so that first aid is needed outside the hospital (pre-hospital). Basic Life Support can be done well if the helper has adequate knowledge. Basic Life Support knowledge is very important for the community, especially common people especially health students. This study aims to determine the level of BHD knowledge in students of the health faculty of the Al Insyirah Institute of Health and Technology. The research method used is descriptive quantitative with a cross sectional approach. The population of this study were all students of the health faculty of the Al Insyirah Institute of Health and Technology using the total sampling method.The results of this study indicate that out of 273 respondents the majority of respondents as many as 118 (43.2%) have knowledge about BHD in the good category.Basic Life Assistance (BHD) can be carried out well if the helper has sufficient knowledge